The strategies of Vietnamese American communities in California in preserving Vietnamese culture 2000-2015 = Các chiến lược của các cộng đồng người Việt ở California trong việc bảo tồn văn hóa Việt Nam giai đoạn 2000-2015 - Vũ, Thị Vân Anh (2021)
The foremost purpose of this paper is to study the significance of Vietnamese American communities in California in the contemporary preservation of Vietnamese culture (2000-2015). To attain this purpose, the researcher has studied a wide range of conceps related to Vietnamese culture and Vietnamese Americans synthesized in the backround chapter, which works as the framework for the further development of the study. The researcher then employs content analysis and visual analysis to deal with previous research. The former analysis strategy is applied to textual materials (mostly online materials) and the latter to non-textual materials such as photos and videos (about 12-16 photos and videos). The findings show that as the context or environment changes, Vietnamese culture also adopts certain self-adjustments in comparison with the native Vietnamese culture. Such differences are explained by the features of Vietnamese American communities as an immigrant group. Additionally, contemporary Vietnamese Americans face difficulties preserving their culture, among which cultural mismatch and acculturative stress are the major ones threatening the Vietnamese language ability among VAs and parental authority. However, the combined efforts made by VA families, community associations and media agencies have facilitated the Vietnamese cultural preservation. In short, the paper provides background and findings of Vietnamese American communities and their culture which are useful for those interested in Vietnamese culture and Vietnamese Americans.